Securing transactions and payment systems for m-commerce - Madan, Sushila 1964-; Arora, Jyoti Batra 1 979- (Advances in e-business research (AEBR) book series, 2016)
This book seeks to present, analyze, and illustrate the challenges and rewards of developing and producing mobile commerce applications, emphasizing the integral role M-commerce plays in global business